The Wanderer - Creech, Sharon; Diaz, DavidBliss, Alan Joseph (New York HarperTrophy, 2000)
Thirteen-year-old Sophie and her cousin Cody record their transatlantic crossing aboard the the Wanderer, a forty-five-foot sailboat, which along with uncles and another cousin, is en route to visit their grandfather in England.
Joana Cotler Books
Keywords: SailboatsEpic poetry, English (Old)